Turning to the UN Security Council: terming crisis a threat to international peace - Aletta Mondré (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
When do states turn to the United Nations Security Council? Today the term threat to peace is interpreted more widely than ever before ranging from inter-state conflict over internal wars to humanitarian crisis. Alarming the Security Council to international crisis is an exceptional foreign policy choice. By far more conflicts are not brought to the attention of the Security Council than are put before that body. The paper explores when states actually turn to the Security Council and term a crisis a threat to international peace. One the one hand, the Security the Council has assumed a much more visible and active role in international dispute settlement since the end of the Cold War. On the other hand, the unilateral decision of the United States to invade Iraq raised serious doubts about the legitimacy and effectiveness of the UN's collective security system. A much repeated truism reminds UN scholars that any system of collective security can be only as good as its members want it to be. But so far we do not have a clear understanding of what its members do want it to be. While the option to involve the UN Security Council in any situation endangering peace is equally open to all states, only some states address the UN in some conflict situations. From this starting point, this paper contributes to the understanding of the role of the UN in fostering conflict resolution as well as shedding light on foreign policy choices by states. In what situations do states turn to the Security Council? Which states take the decision to alert the Council? And what do states want from the Council once they did? Addressing these questions, the paper presents instances in which states decided to turn to the Security Council. The systematic assessment builds on a set of case studies that includes different types of conflict situations in the 1990s as well as different states. States bring crisis situations before the Council which they either perceive as an immediate threat to themselves or as a threat to norms shared by the international community. The paper concludes with some generalizations about reasons for states to turn to the UN Security Council. – – Wann wenden sich Staaten an den Sicherheitsrat der Vereinten Nationen? Heutzutage wird der Begriff Friedensbedrohung umfassender als je zuvor interpretiert. Die Spannbreite reicht von zwischenstaatlichen Konflikten über interne Kriege bis hin zu humanitären Krisen. Dennoch ist es für Staaten eine außergewöhnliche außenpolitische Entscheidung den UN-Sicherheitsrat anzurufen. Nur in sehr wenigen Situationen lenken Staaten die Aufmerksamkeit des Sicherheitsrats auf internationale Krisen. Das Papier untersucht, wann Staaten sich entscheiden, eine Krise dem Sicherheitsrat vorzulegen und diese als Bedrohung für den Weltfrieden zu bezeichnen. Einerseits übernimmt der UN-Sicherheitsrat eine sichtbare und aktive Rolle in der Konfliktbeilegung seit dem Ende des Ost-West-Konflikts, andererseits warf spätestens der Irak-Krieg Zweifel über die Legitimität und Effektivität des Sicherheitsrats auf. Eine Binsenweisheit der UN-Forschung betont, dass eine kollektives Sicherheitssystem nur so gut sein kann wie seine Mitglieder es zulassen. Es ist allerdings noch unklar, welche Vorstellungen die Staaten über das Sicherheitssystem der Uno haben. Obwohl allen Staaten offen steht, jede Krisensituationen dem Sicherheitsrat vorzulegen, nutzen nur einige Staaten in wenigen Situationen diese Möglichkeit. In dieser Ausgangslage trägt das Papier zu einem besseren Verständnis über die Rolle der Uno bei der Konfliktbearbeitung wie auch über außenpolitische Entscheidungen von Staaten. In welchen Situationen wenden sich Staaten an den Sicherheitsrat? Welche Staaten entscheiden sich für die Anrufung des Rats? Und was wollen Staaten dann vom Rat? Das Papier stellt Umstände und Krisen vor, in denen Staaten den Sicherheitsrat angerufen haben. Die systematische Erhebung basiert auf Fallstudien und umfasst verschiedene Typen von Konfliktsituationen in den 1990er Jahren und verschiedene Staaten. Staaten wenden sich an den Sicherheitsrat, wenn sie entweder sich unmittelbar selbst bedroht fühlen oder bei einer Gefährdung von Normen der internationalen Staatengemeinschaft. Die Untersuchung unternimmt zum Ende einen Generalisierungsversuch über die Gründe von Staaten, den Sicherheitsrat anzurufen.
Keywords: 320